The Functional Significance of Shyness in Anorexia Nervosa - Winecoff, Amy A. (Eur Eat Disord Rev, 2015)
The defining features of anorexia nervosa (AN) include disordered eating and disturbance in the experience of their bodies. however, many women with AN also demonstrate higher harm avoidance (HA), lower novelty seeking, and challenges with interpersonal functioning. The current study explored whether HA and novelty seeking could explain variation in disordered eating and social functioning in healthy control women (n = 18), weight-restored women with a history of AN (n = 17), and women currently-ill with AN (AN; n = 17). Our results indicated that clinical participants (AN + weight-restored women) reported poorer social skills than healthy control participants. Moreover, the relationship between eating disorder symptoms and social skill deficits was mediated by HA. Follow-up analyses indicated that only the ‘shyness with strangers’ factor of HA independently mediated this relationship. Collectively, our results suggest a better understanding of shyness in many individuals with eating disorders could inform models of interpersonal functioning in AN.